Non-octahedral-like dislocation glides in aluminum induced by athermal effect of electric pulse. Issue 9 (17th March 2016) - Li, Wei; Shen, Yao; Liu, Haiting; Wang, Yuan; Zhu, Wenjun; Xie, Chaoying
Abstract: Abstract : The dislocation movements under the action of electric pulses (athermal effect) at cryogenic conditions were studied by ex situ transmission electron microscopy (TEM) observations and slip trace analysis innovatively. By applying electric pulses directly through aluminum TEM samples in a liquid nitrogen bath, plenty of non-octahedral-like dislocation glides generally forming at high temperatures (e.g., >453 K for aluminum) were observed at cryogenic temperatures (<130 K). Occurrence of the non-octahedral-like dislocation glides indicates a substantial increase in the degrees of freedom for dislocation glides, offering a new/complementary explanation for the acceleration effect of electric pulses on dislocation movements, especially in the sole athermal effect. In comparison, previous theories relied on extra driving force and/or increased dislocation mobility on the octahedral planes in a face-centered cubic metal. The athermal effects of electric pulse were discussed and the selective heating at the dislocation cores was proposed to account for non-octahedral-like dislocation glides.